Safety and feasibility of laterally extended endopelvic resection for sarcoma in the female genital tract: a prospective cohort study - Soo Jin Park; Junhwan Kim; Jae-Weon Kim; Hee Seung Kim; Ga Won Yim (Korean Society of Obstetrics and Gynecology, 2022)
Objective This study aims to evaluate the safety and feasibility of laterally extended endopelvic resection (LEER) for sarcoma in the female genital tract. Methods We prospectively recruited gynecologic cancer patients with sarcoma arising from female genital tract who underwent LEER at Seoul National University Hospital from December 2016 to March 2021. Clinicopathologic characteristics, surgical outcomes including postoperative complications and pain control, and survival outcomes of the patients were investigated. Results A total of nine patients were registered for this study. The median age was 56 years. Carcinosarcoma (n=2, 22%), leiomyosarcoma (n=2, 22%), and undifferentiated uterine sarcoma (n=2, 22%) were common histology types. Complete resection was achieved in 88.9%. The most common location of pelvic sidewall tumors was infra-iliac acetabulum (66.7%). The pathologic outcome showed a median tumor size of 9.0 cm and internal iliac vessel resection with pelvic sidewall muscle was performed in all patients. The median estimated blood loss was 1,600 mL (range, 300-22,300), and the patients were postoperatively admitted to the intensive care unit for median 1 day (range, 0-8). Complete response was observed in 44.4% (4/9) in radiologic studies after LEER, and median progression-free survival, treatment-related survival, and overall survival were 3.3, 19.6, and 98.9 months, respectively. Conclusion LEER was feasible and safe in treating recurrent sarcoma presenting pelvic sidewall invasion with acceptable survival outcomes and manageable postoperative complications.